Ammonia-oxidizing archaea and bacteria in water columns and sediments of a highly eutrophic plateau freshwater lake - Yang, Yuyin; Li, Ningning; Zhao, Qun; Yang, Mengxi; Wu, Zhen; Xie, Shuguang; Yong Liu (ENVIRONMENTAL SCIENCE AND POLLUTION RESEARCH, 2016)
Both ammonia-oxidizing archaea (AOA) and bacteria (AOB) can play important roles in the microbial oxidation of ammonia nitrogen in freshwater lake, but information on spatiotemporal variation in water column and sediment community structure is still limited. Additionally, the drivers of the differences between sediment and water assemblages are still unclear. The present study investigated the variation of AOA and AOB communities in both water columns and sediments of eutrophic freshwater Dianchi Lake. The abundance, diversity, and structure of both planktonic and sediment ammonia-oxidizing microorganisms in Dianchi Lake showed the evident changes with sampling site and time. In both water columns and sediments, AOB amoA gene generally outnumbered AOA, and the AOB/AOA ratio was much higher in summer than in autumn. The total AOA amoA abundance was relatively great in autumn, while sediment AOB was relatively abundant in summer. Sediment AOA amoA abundance was likely correlated with ammonia nitrogen (rs = 0.963). The AOB/AOA ratio in lake sediment was positively correlated with total phosphorus (rs = 0.835), while pH, dissolved organic carbon, and ammonia nitrogen might be the key driving forces for the AOB/AOA ratio in lake water. Sediment AOA and AOB diversity was correlated with nitrate nitrogen (rs = -0.786) and total organic carbon (rs = 0.769), respectively, while planktonic AOB diversity was correlated with ammonia nitrogen (rs = 0.854). Surface water and sediment in the same location had a distinctively different microbial community structure. In addition, sediment AOB community structure was influenced by total phosphorus, while total phosphorus might be a key determinant of planktonic AOB community structure.